SELF REGULATED LEARNING DALAM AL-QUR’AN - Jamil Abdul Aziz (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
Abstract Self regulated learning is one key to obtaining maximum learning results. However, the facts on the ground are still many students who do not have the independence in learning. Based on this background, it becomes important for every educator and activist education to understand what is the meaning of independent learning, independent learning forms, as well as how to foster independent learning in self-learners.This type of research is the study of literature (libraryresearch). The approach used in this study is the approach of Psychological Sciences. After conducting a study on the independence of existing learning the Koran and Psychology, found some of the following: a) the Koran a lot of gesturing order mankind always read and explore science departing from the awareness and willingness of individuals themselves (QS. [2]: 189, [QS. [8]: 1, [17]: 85) b) forms of learning kemandrian exemplified in al- Koran contained in the story of Moses and Ibrahim (QS. [6]: 76-79). In Psychology, form independent learning contained in Prophet Moses and Nabi Ibrahim belong to the kind Identivied regulation and Intrinsically motivated behavior c) how to cultivate independent learning in the Koran there are: 1) Introduce learners of reality (environment) 2) Build kontsruk think learners Keywords: Self Regulated Learning, The Qur’an.